????? ????? ?? ???????? ???????? ??????? THE MEANINGS OF COMMAND IN HADITS RELATED TO ZAKAT - Rani Ismil Hakim (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2020)
Abstract: Researching the matter is very important in understanding the words of God and the hadiths of the Prophet and deriving legal rulings from them. In this letter, I discussed the matter in terms of its meanings, for the presence of the meanings of the command that depart from its original meaning. It was said: The principle of the matter is to be obligatory, and it was said: The matter is a verb request from the highest to the lowest. If we notice the command words in the Noble Qur’an and the hadiths of the Prophet and Arabic sentences. We find command words that came out of its original meaning. The author specified the search for the meanings of the matter in the hadiths related to zakat, because hadith is the second source of Sharia rulings after the Holy Qur’an. In a statement of what he needs from dairy from its verses. As for zakat, it is one of the five pillars of Islam. ??????? ???????? : ????? ?????? ????????? ??????